OP0221 OLIGOMERIC S100A4 INDUCES MONOCYTE INNATE IMMUNE MEMORY. (June 2019) - Karouzakis, Emmanuel; Pajak, Agnieszka; Riksen, Niels; Joosten, Leo; Netea, Mihai; Lutgens, Esther; Stroes, Eric; Ciurea, Adrian; Distler, Oliver; Grigorian, Mariam; Neidhart, Michel
Abstract : Background: Trained immunity is a process of innate immune memory in which a primary stimulus such as beta-glucan can enhance the response of monocytes to secondary stimuli. The concept that specific damage associated molecular patterns (DAMPs) in rheumatoid arthritis (RA) could cause trained immunity which is involved in the disease pathogenesis has not been investigated so far. The oligomeric form of S100A4 (oS100A4) is a potent inducer of proinflammatory cytokines which is found in the plasma of patients with rheumatoid arthritis (RA). Objectives: Aims are to investigate whether oS100A4 induces trained immunity in monocytes and characterize the molecular pathways involved in this process. Methods: Monocytes were isolated from peripheral blood of healthy donors using anti-CD14 magnetic beads. To induce training, monocytes were stimulated with 2 µg/ml of oS100A4 and 1 µg/ml β-glucan for 24 hours (n=8). We searched for differential gene expression by RNA sequencing in order to identify factors that play a role in the initial stages of trained immunity. On day 4, LPS (10 ng/ml) was added. After 24 hours, IL-6 and TNFalpha were measured in cell culture supernatants by ELISA. The training protocol was repeated in monocytes transfected with PRDM8 siRNA using Lipofectamine (n=4). In addition, plasma levels of S100A4, CCL5 and IL-6 were measured in a cohort of RA patients (n=36) and healthy controls (n=18) by ELISA and PRDM8 transcripts in RA peripheral blood monocytes were quantified by RT-PCR. Results: Monocytes primed with oS100A4 showed increased releases of IL-6 and TNFalpha in response to a subsequent LPS stimulation. RNA-Seq revealed the differential expression of 902 genes upon oS100A4 and 667 upon beta-glucan (mean and median > 2 fold, p<0.01). Among the differential genes, 601 were upregulated in S100A4 and 447 in beta-glucan stimulated cells. Upregulated genes included chemokine/cytokine and epigenetic factors. When we compared the upregulated genes from oS100A4 and beta-glucan stimulated cells, 83% of chemokines/cytokines and 50% epigenetic factors were identical. Interestingly, the histone methyltransferase PRDM8 was found to be a major regulator of pro-inflammatory mediators by both stimuli. siRNA knockdown of PRDM8 abolished the training effect of oS100A4 by decreasing the LPS induced release of IL-6 and TNFalpha (p<0.01). Furthermore, we analyzed a cohort of monocytes taken from RA patients. Higher PRDM8 transcription in RA monocytes was associated with increased plasma levels of CCL5 and IL-6 (r = 0.52 and 0.55, p < 0.01). RA patients in remission versus active patients showed significantly lower PRDM8 transcripts (p < 0.05). Conclusion: Oligomeric S100A4 induced trained immunity in monocytes similarly to beta-glucan. PRDM8 histone methyltransferase is involved in this process that appears to be activated in monocytes of RA patients. Disclosure of Interests: Emmanuel Karouzakis: None declared, Agnieszka Pajak: None declared, Niels Riksen: None declared, Leo Joosten: None declared, Mihai Netea: None declared, Esther Lutgens: None declared, Eric Stroes: None declared, Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Mariam Grigorian: None declared, Michel Neidhart: None declared